Penanaman Tanaman TOGA Guna Mencegah Stunting Di Desa Arul Kumer Selatan - Hikmah, Hikmah; Syahputra, Syahdan (Universitas Gajah Putih, Indonesia, 2024)
Stunting is an irreversible growth disorder that can be influenced by many factors, one of which is influenced by insufficient nutrition. One of the efforts made to prevent stunting is by planting TOGA plants in the yard.Planting TOGA plants is useful for preventing stunting because it can be used as a fitness drink, a concoction for minor health problems, and maintaining health, as well as improving nutrition. So it is safe for consumption, both by pregnant women and babies or toddlers. Planting TOGA plants in the home yard will influence the amount and type of variation in nutritional intake for toddlers, thereby avoiding chronic malnutrition and stunting.